DOES LOAN-TO-VALUE SUPPORT FINANCIAL STABILITY IN INDONESIA? - AGUS SALIM; IGNATIUS ABASIMI; LESTARI SUKARNIATI; NAVEED ASLAM (LP2MTBM MAKARIOZ, 2023)
One of which is loan to value (LTV). The implementation helps to improve financial stability. Our study analyses the impact of LTV on banking financial stability. We employ panel GMM-System to reduce the bias of analysis for eighteen commercial banks from 2004 to 2019. The result shows that the LTV instrument confirms an improvement effect on the financial stability index. It implies that the more tighten policy on mortgage and vehicle loan, the more stable financial system especially in banking sector in Indonesia.